SOCIAL AND ECONOMIC NATURE OF SMALL BUSINESS (Journal of Universal Science Research, 2024)
This article explores the socio-economic nature of small businesses, emphasizing their role in economic development, community engagement, and social cohesion. Through a detailed examination of their economic contributions and social impacts, the article highlights the importance of small businesses in fostering innovation, creating employment, and supporting local communities. The analysis is based on recent research and case studies that illustrate the multifaceted influence of small enterprises.